2016
DOI: 10.1177/1362361315611381
|View full text |Cite
|
Sign up to set email alerts
|

Does sex influence the diagnostic evaluation of autism spectrum disorder in adults?

Abstract: It is unknown whether sex influences the diagnostic evaluation of autism spectrum disorder, or whether male and female adults within the spectrum have different symptom profiles. This study reports sex differences in clinical outcomes for 1244 adults (935 males and 309 females) referred for autism spectrum disorder assessment. Significantly, more males (72%) than females (66%) were diagnosed with an autism spectrum disorder of any subtype (x2 = 4.09; p = 0.04). In high-functioning autism spectrum disorder adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 45 publications
5
70
0
4
Order By: Relevance
“…A major finding of ours was that females with ASD were far more likely to receive psychotropic medications than males, even when controlling for specific comorbidities. This could be additional support to the growing evidence that ASD is underdiagnosed in females [Begeer et al, ; Gould & Ashton‐Smith, ; Wilson et al, ]. In a recent meta‐analysis, Loomes, Hull, and Mandy [] concluded that the true male to female ratio in ASD is closer to 3:1, rather than 4:1, which we observed in this study.…”
Section: Discussionsupporting
confidence: 88%
“…A major finding of ours was that females with ASD were far more likely to receive psychotropic medications than males, even when controlling for specific comorbidities. This could be additional support to the growing evidence that ASD is underdiagnosed in females [Begeer et al, ; Gould & Ashton‐Smith, ; Wilson et al, ]. In a recent meta‐analysis, Loomes, Hull, and Mandy [] concluded that the true male to female ratio in ASD is closer to 3:1, rather than 4:1, which we observed in this study.…”
Section: Discussionsupporting
confidence: 88%
“…Other reports (Brereton et al, 2006;Dworzynski et al, 2012) similarly noted that females with ASD are just as likely as males with ASD to demonstrate disruptive behavior and attentional deficit and hyperactivity, a pattern different from that found in typically developing boys and girls. A recent study of adults reported that in a large clinic referred sample of adults, women were significantly less likely to receive a diagnosis of ASD after being referred for an evaluation (Wilson et al, 2016). The sum of these findings also mirrors conclusions from research on attention deficit hyperactivity disorder (ADHD).…”
Section: Role Of Implicit Biassupporting
confidence: 57%
“…This study was cross‐sectional, specific to high functioning males with ASD, lacked pubertal developmental measures [Urosevic et al, ] and did not include a semi‐structured clinical interview of possible psychiatric comorbidity such as the SCID‐5‐RV. Hence, our findings describe age‐related differences that may not generalize to others within the autism spectrum, including females [Craig et al, ; Ecker et al, ; Wilson et al, ]. However, study strengths include the relatively large sample of physically healthy, medication naive, clearly diagnosed males with ASD without confounding psychiatric diagnoses and matched controls, and the 25 year age span from childhood to adulthood.…”
Section: Limitationsmentioning
confidence: 86%